Children and their development - Kail, Robert V. (Upper Saddle River, NJ Pearson Education/Prentice Hall, 2007)
[This text] uses[s] fundamental developmental issues as a foundation for integrating the many discoveries that make child-development science a dynamic field. [It] explain[s] many different methods used by researchers, then illustrate[s] them repeatedly to drive home the lesson that progresses when complementary methods coverage. [It also] demonstrate[s] that the results of child-development research can be used to enhance the lives of children and their families. -Pref
Science of child development -- Genetic bases of child development -- Prenatal development, birth, and the newborn -- Growth and health -- Perceptual and motor development -- Theories of cognitive development -- Cognitive processes and academic skills -- Intelligence and individual differences in cognition -- Language and communication -- Emotional development -- Understanding self and others -- Moral understanding and behavior -- Gender and development -- Family relationships -- Influences beyond the family -- Glossary
Includes bibliographical references (p. 501-524) and indexes
Keywords: Child development; Memory in children; Cognition in children